Diferenças Entre os Depósitos Auríferos do Grupo Aguapei (Estado de Mato Grosso) e os Clássicos Exemplos de Ouro em Conglomerados - FERNANDES, CARLOS JOSÉ; PULZ, GÊNOVA MARIA; KUYUMJIAN, RAUL MINAS; PINHO, FRANCISCO EGÍDIO CAVALCANTE (Pesquisas em Geociências, 2005)
<!-- .p { text-align: justify; } --> Gold prospects in the Aguapeí Folded Belt are situated in the southwestern portion of the Amazon Craton, within the Alto Guaporé Province, southwestern state of Mato Grosso. The mineralizations are mainly concentrated in the Pau-a-Pique Deposit (south), Lavrinha Region (central), and São Vicente Mine (north). Gold ore comprises quartz veins and disseminations in the low-grade metamorphic metassedimentary rocks from the Aguapeí Group. This stratigraphic unit was strongly deformed by the Sunsás-Aguapeí Orogeny (1.28-0.95 Ga). The Aguapeí gold deposits differ in their petrography, chemistry, structural aspects and age from world classic gold deposits associated with coarse clastic sedimentary sequences (Witwatersrand, Jacobina, Tarkwa, etc.). This study discusses the main differences between Aguapeí gold deposits and the classic worldwide deposits hosted by conglomerates.